PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADA BEBEK SURAMADU SAMBEL PENCIT DI KOTA BANGKALAN MADURA - Halimatus Saleha; Dyahrini Prihastuty (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
In Indonesia, there are currently many types of industries that are increasingly modern, one of which is theculinary industry. The culinary industry has recently developed very rapidly, because the culinary industry is considered quite promising because it offers products that are basic for every human being, namely food and drink. Enjoying fast food is no longer to fulfill primary needs but also a lifestyle, where fast food restaurants have become a very popular gathering place. Bebek Suramadu Sambel Pencit is one of the fast food restaurants in Bangkalan Madura.This research aims to analyze the influence of product quality, price perception, and location which have asignificant effect on customer satisfaction with Bebek Suramadu Sambel Pencit in the city of Bangkalan, Madura, both partially and simultaneously. This research was conducted on customers from Bebek Suramadu Sambel Pencit in Bangkalan City, Madura. With a sample size of 100 respondents who were collected using a questionnaire and the analysis techniques used were Validity Test, Reliability Test and Multiple Linear Regression with SPSS 27.The results of this research: Product Quality, Price Perception and Location simultaneously have a significant effect on Customer Satisfaction. Customers for Bebek Suramadu Sambel Pencit in the city of Bangkalan Madura. Product Quality partially has a significant effect on Customer Satisfaction. Customers for Bebek Suramadu Sambel Pencit in the city of Bangkalan Madura. , Price Perception partially does not have a significant effect on Customer Satisfaction. Customers at Bebek Suramadu Sambal Pencit in the city of Bangkalan, Madura. Location partially has a significant effect on Customer Satisfaction. Customers at Bebek Suramadu Sambel Pencit in the city of Bangkalan, Madura.